2022
DOI: 10.3390/ijms23137054
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomic Analysis of SAUR Gene Family, Cloning and Functional Characterization of Two Genes (PbrSAUR13 and PbrSAUR52) in Pyrus bretschneideri

Abstract: The SAUR (small auxin-up RNA) gene family is the biggest family of early auxin response genes in higher plants and has been associated with the control of a variety of biological processes. Although SAUR genes had been identified in several genomes, no systematic analysis of the SAUR gene family has been reported in Chinese white pear. In this study, comparative and systematic genomic analysis has been performed in the SAUR gene family and identified a total of 116 genes from the Chinese white pear. A phylogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…Previous studies also revealed 52, 60, 62, and 68 SAUR proteins in pineapple, grape, cucumber, and wax gourd [17,23,25,27]. Meanwhile, a total of 98, 105, and 116 putative SAUR proteins was found in apple, poplar and Chinese white pear [16,20,47]. Our comparisons suggested that the SAUR families in higher plant species were large groups, with greatly variable members.…”
Section: Identification and Annotation Of Tcsaur Genes In Cacaosupporting
confidence: 71%
See 4 more Smart Citations
“…Previous studies also revealed 52, 60, 62, and 68 SAUR proteins in pineapple, grape, cucumber, and wax gourd [17,23,25,27]. Meanwhile, a total of 98, 105, and 116 putative SAUR proteins was found in apple, poplar and Chinese white pear [16,20,47]. Our comparisons suggested that the SAUR families in higher plant species were large groups, with greatly variable members.…”
Section: Identification and Annotation Of Tcsaur Genes In Cacaosupporting
confidence: 71%
“…Interestingly, the chromosomal distributions of the SAUR gene family in the genomes of other higher plant species, such as coffea [19], melon [21], and wax gourd [23] also confirmed our finding. Previously, the SAUR family is being explored in various higher plant species, such as potato [12], tomato [12], watermelon [13], cotton [14], moso bamboo [15], poplar [16], grape [17], apple [18], coffea [19], Chinese white pear [20], melon [21], loquat [22], wax gourd [23], peanut [24], pineapple [25], foxtail millet [26], cucumber [27], and longan [28]. More specifically, 31 and 38 members of the SAUR families have been recorded in coffea and moso bamboo [15,19].…”
Section: Identification and Annotation Of Tcsaur Genes In Cacaomentioning
confidence: 99%
See 3 more Smart Citations